Anti-Candida activity assessment of Pelargonium graveolens oil free and nanoemulsion in biofilm formation in hospital medical supplies. (November 2016) - Giongo, Janice Luehring; de Almeida Vaucher, Rodrigo; Fausto, Viviane Pedroso; Quatrin, Priscilla Maciel; Lopes, Leonardo Quintana Soares; Santos, Roberto Christ Vianna; Gündel, André; Gomes, Patrícia; Steppe, Martin
Abstract: Infections due to microbial biofilm formation on the surface of catheters and other medical devices are constantly reported as a major cause of morbidity and mortality in patients admitted to hospitals. Furthermore, sessile cells are more resistant to phagocytosis and most antimicrobial, which complicates the treatment of such infections. Researches aimed at new antimicrobial originating mainly from plants have increased in recent years and the development of new strategies for their release is critical in combating the formation of biofilms. Geranium oil (GO) has proven antimicrobial activity. Because of this, the aim of this study was to develop nanoemulsions containing this oil (NEG) and evaluate its activity after the biofilm formation of Candida albicans, Candida tropicalis, Candida glabrata, and Candida krusei in hospital medical supplies. For quantification of the biofilm, crystal violet, total protein, and ATP-bioluminescence assays were used. The results revealed that GO and NEG showed lower MIC for C. albicans and C. tropicalis . The biofilms formed by different species of Candida on the surfaces of polyethylene and polyurethane were quantified. GO and NEG significantly inhibited the formation of biofilms in all species tested on the surfaces of polyethylene. However, NEG antibiofilm has had better activity than GO for C. albicans, C. tropicalis and C. glabrata, according to the surface potential analysis by atomic force microscopy (AFM). The analysis of the biofilm formation on the polyethylene surface by ATP-bioluminescence and CFU showed similar results. In both methods the formation of biofilm in the catheter occurred in greater quantity for C. albicans and C. tropicalis. GO did not significantly inhibit the formation of biofilms only in C. krusei, although NEG significantly increased this activity GO in all species tested when compared to the control training biofilm. The following study shows that the development of NEG may become an effective alternative to reduce the adhesion of microorganisms and prevent infections resulting from the use of some hospital medical materials. Highlights: The geranium oil (GO) and nanoemulsion of geranium oil (NEG) showed antifungal activity against different Candida species. Nanoemulsion containing geranium oil (NEG) reduced the formation of biofilm Candida albicans and Candida krusei in the polyurethane catheters. NEG seems a novel strategy for effectively eliminate biofilm formation and prevent growth of microorganisms on catheters.